LITERARY TRANSLATION AND ITS PROBLEMS - Usarova Muxlisaxon; To’raxon Abduraxmonov (TADQIQOTLAR, 2025)
Abstract;  Literary  translation  plays  a  vital  role  in  ensuring  intercultural understanding, the exchange of artistic values, and the global circulation of literary heritage.  As  literature  embodies  not  only  linguistic  structures  but  also  a  nation’s cultural  memory,  worldview,  emotional  depth,  and  aesthetic  principles,  translating literary  works  from  one  language  into  another  presents  unique  complexities.  This research  explores  the  fundamental  nature  of  literary  translation,  emphasizing  its creative dimension and the translator’s responsibility as both an interpreter and a co-creator of meaning. The study examines the major linguistic, stylistic, cultural, and poetic challenges faced by translators. These include the difficulty of rendering author-specific styles, idiomatic  expressions,  metaphors,  wordplay,  cultural  realia,  dialectal  features,  and character-specific  speech  patterns.  Particular  attention  is  given  to  the  issue  of preserving national color and connotative meaning, which often resist direct translation and require culturally sensitive strategies such as adaptation, functional equivalence, or explanatory translation.